Value of a standard urinary dipstick test for detecting microalbuminuria in patients with newly diagnosed hypertension - Sigle, JP (Swiss medical weekly, 2005)
Microalbuminuria may indicate target organ damage in hypertensive patients. However, testing for microalbuminuria is not yet consistently used in general practice. This may be partly due to a lack of data regarding the diagnostic value of practice-based dipstick testing in newly diagnosed hypertension. Objectives were to assess the diagnostic value of a standard dipstick test for urinary protein excretion. 186 patients who had been newly diagnosed with hypertension were screened for microalbuminuria. A spot urine sample from each of the subjects was evaluated by using a standard dipstick test (Combur 10, Roche Diagnostics GmbH, Mannheim, Germany) in a primary care setting. The albumin/creatinine ratio was used as the "gold standard". Dipstick testing for protein was positive in 31 urine samples (16.7% of the test samples). The albumin/creatinine ratio was elevated in 33 samples (17.7% of the test samples). The sensitivity of detecting microalbuminuria was 26%, specificity 89%, positive predictive value 45%, and the negative predictive was 88%. Repeated dipstick testing 48 hours after the initial testing in 40 randomly selected patients showed a good reproducibility (98%). In a primary care setting a positive standard dipstick test of a random spot urine in patients with newly diagnosed hypertension may indicate the presence of microalbuminuria with high specificity. However, because of its low sensitivity, the standard urinary dipstick test can not be recommended as the sole method of screening for renal target organ damage. In addition standard dipstick testing is important to exclude confounding factors that can falsify the measurement of urinary protein excretion.